Who will remember - Harris, C. S. (Harris, C. S. Sebastian St. Cyr mystery series, 2025)
August 1816. England is in the grip of what will become known as the Year Without a Summer. Facing the twin crises of a harvest-destroying volcanic winter and the economic disruption caused by the end of the Napoleonic Wars, the British monarchy finds itself haunted by the looming threat of bloody riots not seen since the earliest days of the French Revolution. Amidst the turmoil, a dead man is found hanging upside down by one leg in an abandoned chapel, his hands tied behind his back. The pose eerily echoes the image depicted on a tarot card known as Le Pendu, the Hanged Man. The victim--Lord Preston Farnsworth, the younger brother of one of the Regent's boon companions--was a passionate crusader against what he called the forces of darkness, namely criminality, immorality, and sloth. His brutal murder shocks the Palace and panics the already troubled populace. Sebastian St. Cyr, Viscount Devlin, learns of the murder from a ragged orphan who leads him to the corpse and then disappears. At first, everyone in the dead man's orbit paints Lord Preston as a selfless saint. But as Sebastian delves deeper into his life, he quickly realizes that the man had accumulated more than his fair share of enemies, including Major Hugh Chandler, a close friend who once saved Sebastian's life. Sebastian also discovers that the pious Lord Preston may have been much more dangerous than those he sought to redeem. As dark clouds press down on the city and the rains fall unceasingly, two more victims are found, one strangled and one shot, with ominous tarot cards placed on their bodies. The killer is sending a gruesome message and Sebastian is running out of time to decipher it before more lives are lost and a fraught post-war London explodes"--